Buffalo powder dairy products with and without lactose hydrolysis: Physical-chemical and technical-functional characterizations. (November 2021) - Lima de Paula, Igor; Scaldini Teixeira, Eduarda Barbosa; Francisquini, Júlia d'Almeida; Stephani, Rodrigo; Perrone, Ítalo Tuler; Fernandes de Carvalho, Antônio; Cappa de Oliveira, Luiz Fernando
Abstract: Buffalo milk is the second most consumed type of milk in the world, behind only bovine milk. However, expertise in the production and physicochemical characteristics of buffalo milk powder products are not yet widely explored. Characterization techniques of three products were carried out in order to understand their composition of them after production. Raman spectroscopy accompanied by chemometrics was essential to understand the crystallization process of lactose in different environments with varying relative humidity. Finally, hydrolyzed products showed worse browning and rehydration rates as well as a worsening of rehydration when compared to the product without hydrolysis, in addition to the fact that maltodextrin served to circumvent these problems in the hydrolyzed product in two storage conditions in this work. Highlights: Buffalo's milk powder with and without lactose were investigated. Raman spectroscopy has been used to evaluate the lactose crystallization. Compositional analysis after production has also been determined. Different storage conditions leave to a Maillard's reaction improvement. Different water activity values provide a better lactose crystallization.